What is the optimal number of lymph nodes to be dissected in colorectal cancer surgery? - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2005)
Background: Regional lymph node (LN) involvement in colorectal cancer (CRC) identifies the stage and the subset of patients who would benefit from adjuvant chemotherapy. We performed a retrospective analysis to determine if the number of recovered LNs was associated with long-term outcome in patients operated on for stage II and III CRC. Patients and methods: Hospital records of 179 patients with CRC followed in our unit from 1997 to April 2003 were reviewed. Results: On average 11.68 +/- 7.3 LNs were sampled per surgical specimen. Sampling of at least nine LNs appeared to be the minimum number required for accurately predicting LN involvement (P = 0.002). Three-year rates of disease-free survival (DFS), local recurrence-free survival (LRFS) and overall survival (OS) were lower in patients with fewer than nine LNs sampled (P = 0.032, P = 0.006 and P = 0.04, respectively). However, this had no impact on the three-year distant metastasis-free survival rate (DMFS) (P = 0.472). In stage II disease, patients with nine or more LNs dissected had significantly higher three year DFS and LRFS rates than the subgroup with fewer than nine LNs dissected (P = 0.024 and P = 0.015, respectively), but this did not have any effect on DMFS or OS (P = 0.406 and P = 0.353, respectively). Conclusion: Current protocols provide adjuvant treatment in stage III patients; the problem is to correctly determine stage by recovering as many LNs as possible.
Keywords: colorectal cancer; lymph nodes; lymph node excision; local recurrence; MINIMUM NUMBER; COLON-CANCER; RESECTION SPECIMENS; CARCINOMA; ADENOCARCINOMA; RECOMMENDATION; RECOVERY